Changing Meanings of Megalithic Monuments in the Kelabit Highlands of Sarawak - Nicholas, Gani (Penerbit UKM, Bangi, 2025)
This book examines contemporary engagements with the megalithic monuments in the Kelabit Highlands of Sarawak, Malaysian Borneo. It proceeds from the premise that over the long term, despite being objects that originated in the past, megalithic monuments are capable of accumulating new meanings as a result of their interactions with different groups of people in different times and contexts. The creation and recreation of the meanings of the megalithic monuments are shown to be the products of historical and contemporary processes that are tied to the political, social, economic and environmental changes that the region and its inhabitants have experienced since colonial times to the present day. By focusing on local and contemporary interactions with the megalithic monuments, this book provides an up-to-date ethnography that broadens understanding of the social significance of megalithic monuments as multivalent objects, and addresses the wider issue of how people relate to and make meanings of objects from the past.